Neuromodulation of the Feedforward Dentate Gyrus-CA3 Microcircuit - Prince, Luke Y.; Bacon, Travis J.; Tigaret, Cezar M.; Mellor, Jack R. (Frontiers in Synaptic Neuroscience, 2016)
The feedforward dentate gyrus-CA3 microcircuit in the hippocampus is thought to activate ensembles of CA3 pyramidal cells and interneurons to encode and retrieve episodic memories. The creation of these CA3 ensembles depends on neuromodulatory input and synaptic plasticity within this microcircuit. Here we review the mechanisms by which the neuromodulators aceylcholine, noradrenaline, dopamine, and serotonin reconfigure this microcircuit and thereby infer the net effect of these modulators on the processes of episodic memory encoding and retrieval.